Long-term (>10-year) clinical follow-up after young embolic stroke/TIA of undetermined source. Issue 1 (January 2021) - Nassif, M; Annink, ME; Yang, H; Rettig, TCD; Roos, YBWEM; van den Brink, RBA; Tijssen, JGP; Mulder, BJM; de Winter, RJ; Bouma, BJ
Background: To date, the pathophysiology of first-ever and recurrent stroke/TIA still remains unclear in young patients with embolic stroke/TIA of undetermined source (ESUS). Clinical studies with long-term follow-up in young ESUS patients are necessary to investigate the underlying pathophysiology of first-ever and recurrent stroke/TIA in this patient population, in particular the role of new-onset atrial fibrillation. Aims: Our aim was to study the long-term (>10-year) clinical outcome of young patients (<50 years) with ESUS. Methods: This cohort study included all patients aged ≤ 50 years who underwent transoesophageal echocardiography for diagnostic work-up of ESUS during 1996–2008 from one tertiary center. All patients were contacted by telephone between September–November 2018 to update clinical information from medical records. The clinical outcomes of this study were incidence rates of all-cause and cardiovascular mortality, recurrent stroke/TIA, new-onset clinical AF, and ischemic vascular events. Results: In total, 108 patients (57% female, mean age 40 ± 7.2 years [range 19–50 years], n = 72 stroke) were included. Across clinical follow-up (median 13[IQR 10–16] years), 24 patients died ( n = 14 cardiovascular). The 15-year incidence rate of recurrent stroke/TIA was 15% (incidence rate = 1.09[95%CI 0.54–1.65]/100 patient-years) and a 5.5% incidence of new-onset clinical AF (incidence rate = 0.44[95%CI 0.09–0.79]/100 patient-years) following ESUS. Conclusions: The incidence of recurrent stroke/TIA is relatively high during long-term clinical follow-up of young patients with ESUS. In contrast, new-onset clinical AF is relatively low and therefore may not play an important part in the pathophysiology of first-ever and recurrent stroke/TIA of these patients.